(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The active participation of students is an inherent requirement of any educational intervention. Indeed, active teaching and working in subgroups is a method which promotes motivation among students in active informal learning. In this study, we have shown that the subgroups work, as a means of active learning, has improved student performance as well as a self-efficacy to control the content.